Effect of adding fortifiers and protein supplements on the osmolality of donated maternal milk - Ester Torres Martínez; Ana Alejandra García Robles; María Gormaz Moreno; Ana Gimeno Navarro; Isabel Izquierdo Macián; José Luis Poveda Andrés; Máximo Vento (Elsevier, 2020)
Introduction and objectives: The fortification of maternal milk (MM) is a standard practice in order to achieve the requirements needed for the growth and development of the premature newborn. However, its osmolality could increase. According to the American Paediatrics Academy, it is recommended not to exceed 450 mOsm/kg (approximately 400 mOsm/L) in the diet of the infant, even though the safety limit is estimated to be between 400 and 600 mOsm/kg.The aim of this study is to determine the osmolality of thawed and fortified donated MM (DMM). Method: An analysis was performed on DMM of 6 healthy mothers, without fortifying, and with 4 levels of fortification. Measurement of the samples was carried out in triplicate at 0, 4, 9, and 24 h after their preparation. They were stored refrigerated (2-8 °C) between measurements. The study groups were: (A) non-fortified DMM; (B) DMM with vitamins added; (C) with the addition of a fortifier; (D) with the addition of a low-dose protein formula; and (E) with the addition of a high-dose protein formula. The osmolality determinations were carried out using a freezing-point osmometer. The data analysis was performed using R software (v.3.5.1). Results: A total of 30 samples were analysed with 360 measurements. The osmolality of the DMM at t = 0 h was 301 mOsm/kg (SD 5.2) and slightly increased with time to 308.11 mOsm/kg (SD 5.21) after 24 h (t = 24 h), being maintained within the safety limits. The addition of vitamins (Group B) did not significantly increase the osmolality. The addition of a fortifier (C) and a low dose (D) or high dose (E) protein formula produced an increase in the baseline osmolality that increased statistically significantly in time (P = .007), but with no differences between the C, D, and E types. There were differences between the osmolality at t = 0 with the fortification according to the manufacturer's data sheet (339 mOsm/L) and the findings in our laboratory (432.33 mOsm/L). Conclusion: The osmolality values found in the thawed DMM samples were similar to those of other studies. The fortification of the DMM samples and their storage refrigerated at 2-8 °C for 24 h increased the osmolality, but keeping them within the safety limits. Resumen: Introducción y objetivos: La fortificación de la leche materna (LM) es una práctica habitual para alcanzar los aportes necesarios para el crecimiento y desarrollo del recién nacido prematuro. Sin embargo, puede aumentar su osmolalidad. Según la Academia Americana de Pediatría, se recomienda no superar 450 mOsm/kg (aproximadamente 400 mOsm/l) en la alimentación del lactante, aunque el límite de la seguridad se estima entre 400-600 mOsm/kg.El objetivo de este estudio es determinar la osmolalidad de la LM donada (LMD) descongelada y fortificada. Método: Se analizó la LMD de 6 madres sanas, sin fortificar y con 4 pautas de fortificación, realizando mediciones por triplicado de las muestras a tiempo 0, 4, 9 y 24 h tras su preparación. Entre mediciones se almacenó refrigerada (2-8 °C). Los grupos de estudio fueron: 1) A: LMD no fortificada; 2) B: LMD con adición de vitaminas; 3) C: con adición de fortificante; 4) D: con adición de módulo proteico a dosis baja, y 5) E: con adición de módulo proteico a dosis alta. Las determinaciones de osmolalidad se realizaron un osmómetro crioscópico. El análisis de datos se realizó con R software (v.3.5.1). Resultados: Se analizaron un total de 30 muestras (360 mediciones). La osmolalidad de la LMD a t = 0 h fue 301 mOsm/kg (DE 5,2) y aumentó ligeramente con el tiempo a 308,11 mOsm/kg (DE 5,21) después de 24 h (t = 24 h), manteniéndose en los límites de seguridad. La adición de vitaminas no aumentó la osmolalidad de manera significativa (grupo B). La adición de fortificante (C) y módulo de proteínas con dosis baja (D) o dosis alta (E) produjo un aumento de osmolalidad basal que se incrementó en el tiempo de manera estadísticamente significativa (p = 0,007) pero sin diferencias entre los tipos C, D y E. Hubo diferencias entre la osmolalidad en t = 0 con la fortificación según la ficha técnica del fabricante (339 mOsm/l) y los hallazgos en nuestro laboratorio (432,33 mOsm/l). Conclusión: Los valores de osmolalidad hallados en las muestras de LMD descongelada son similares a los de otros estudios. La fortificación de la LMD y su conservación refrigerada entre 2-8 °C durante 24 h aumenta la osmolalidad, pero manteniéndose dentro de los límites de seguridad.